Efficacy of wound cleanser 25% based on indonesian medicine plants on chronic wound healing - Julianto, Eko; Suandika, Made; Agustin, Ayu Tri; Julianus, Julianus; Riranto, Jepri (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
ABSTRACT Background: Chronic wounds are a challenge for wound care professionals and a global economic burden that has increased morbidity and mortality in patients worldwide. Purpose: This study aims to determine the efficacy of wound cleanser with guava leaf extract (Psidium guajava Linn) and betel leaf extract (Piper betle L) 25% on the inhibition of bacterial growth in chronic wounds. Methods: The research conducted was laboratory experimental in nature. Guava leaf extract (Psidium guajava Linn) and betel leaf extract (Piper betle L) were formulated in the form of liquid soap with a concentration of 25% then evaluation of the physical preparations, allergy tests and bacterial tests were carried out in the form of the inhibition of liquid soap against Pseudomonas aeruginosa bacteria, Staphylococcus aureus, Escherichia coli in chronic wounds, Bacillus subtilis, Bacillus cereus, Staphylococcus epidermidis and Yeast Candida Albicans. Data collection is carried out after passing the ethical test. Results: This proves that liquid soap preparations of ethanol extract of guava leaves (Psidium guajava Linn) and betel leaf extract (Piper betle L) have medium, strong and very strong inhibition against Pseudomonas aeruginosa (12.28 mm), Staphylococcus aureus (19.48 mm), Escherichia coli (13.94 mm), Bacillus subtilis (27.58 mm), Bacillus cereus (11.11 mm), Staphylococcus epidermidis (14.44 mm) and category of respond medium inhibition on Yeast Candida Albicans (8.13 mm). Conclusion: Based on the results of the study, it can be concluded that the formulation of liquid soap preparations of ethanol extract of guava leaves (Psidium guajava Linn) and betel leaf extract (Piper betle L) with a concentration of 25% fulfills the quality requirements for liquid soap preparations. The results of this liquid soap antibacterial test had a strong response in inhibiting the growth of the bacteria Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Staphylococcus epidermidis. Keywords: Liquid soap, Psidium guajava Linn, Piper betle L, Bacteria